THE STATE OF DENTAL HEALTH IN CHILDREN AND OPPORTUNITIES FOR ITS IMPROVEMENT IN THE CASE OF ANDIJAN REGION (International journal of medical sciences, 2025)
This study was devoted to studying the dental health status of children aged 3-15 years in Andijan region and identifying opportunities for its improvement. The study analyzed 1250 children in different regions of the region and studied their prevalence of dental diseases, risk factors and their association with family and social factors. The results showed differences between the dental health of children in urban and rural areas, low oral hygiene skills and shortcomings in the use of dental services. Based on the results of the study, comprehensive measures were proposed to improve the dental health of children.